Swashby and the sea - Ferry, Beth (Houghton Mifflin Harcourt, 2020)
No-nonsense Captain Swashby is used to the sea meeting all of his needs and when, after his retirement, new neighbors disturb his solitary life, the sea helps in just the right way.